General interaction mode of CIDE:CIDE complex revealed by a mutation study of the Drep2 CIDE domain. Issue 7 (26th February 2013) - Lee, Seung Mi; Park, Hyun Ho
Abstract : Drep2 and Drep1 bind by blue native page (View interaction) Abstract : ► We found that surface of the CIDE domain can be divided into a basic side and an acidic side. ► We found that the basic surface side of Drep2 CIDE is responsible for the interaction with Drep1 and Drep3. ► We conclude that charge–charge interaction might be the general interaction mode for CIDE:CIDE interaction.